How to Recognize and Prevent Multiple Sclerosis Disease - Rakeeh Ghaderi; Azam Alikhademi (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
The increasing incidence of multiple sclerosis (MS) worldwide, especially in women, points to the crucial role of environmental and lifestyle risk factors in determining the disease occurrence. MS is an unpredictable disease that affects people differently. Some people with MS may have only mild symptoms. Others may lose their abilities such as clear vision, writing, speaking, or walking when communication between the brain and other parts of the body becomes disrupted. This study was an attempt to examine the effective factors of the Multiple Sclerosis diseases. The participants of the study were selected from among a total number of 45 men and women who were treated in a health center in Azarbayegan and Damavand in Iran. In order to study, the researchers applied various procedures to collect the data of the study. The participants were interviewed and filled out the questionnaires. After categorizing and classifying the collected information and data, it was processed and analyzed and finally, the results were found. To test the research questions, a one-sample T-test was used to analyze the data. The role of hypovitaminosis D as a possible risk factor for multiple sclerosis was reviewed. First, it was emphasized that hypo vitamin could be only one of the risk factors for multiple sclerosis and that numerous other environmental and genetic risk factors appear to interact and combine to trigger the disease. The main aim of this study was to examine the effective factors of Multiple Sclerosis diseases. The methodology of this research was to test the research questions; a one-sample T-test was used to analyze the data. The findings of this study revealed that the factors of gender, cold weather, vitamin D deficiency, and age (between 30 - 59) were effective on the Multiple Sclerosis diseases. According to more detailed studies, the researchers found that vitamin D deficiency plays an important role in Multiple Sclerosis. Cold weather is an important factor in contracting and aggravating for this disease. In the study of gender composition in the regions, the researchers found that the probability of infection is higher among women than men. Therefore, women can reduce the chance of infection by preventing the progression of other factors. Age can be a complementary factor if a person has not been diagnosed with this disease until the age of 30. It can be predicted that this person will not come down with this disease again.